The First Swedish Translation from the Lunyu - Nordvall, Christian ca. 20./21. Jh. (Journal of the American Oriental Society, 2023)
This paper describes the first known translation from the Confucian classics into Swedish, a collection of eighty quotations from the Lunyu published as an appendix to J . A . Bellman's Wishetenes råd (1707). The work is a third-generation translation, made from the French La morale de Confucius (1688), which is itself an abridged translation of the Latin Confucius Sinarum philosophus (1687). This paper selects ten of the eighty quotations for detailed analysis and commentary. The main findings are that the translation removes so much of the Chinese context and Confucian technical vocabulary that the text becomes almost indistinguishable from generic wisdom literature. Furthermore, the Swedish translator adds a layer of "Christian" vocabulary, which was not present in the Latin and French versions. However, at a time when Sweden had almost no contact with non-Christian cultures, the translation may have played a valuable role in making the Swedish public positively disposed toward Chinese culture .